Physico-chemical properties of the top 120 m of two ice cores in Dronning Maud Land (East Antarctica) - Wauthy Sarah; Tison Jean-Louis; Inoue Mana; El Amri Saïda; Sun Sainan; Claeys Philippe; Pattyn Frank (Zenodo, 2023)
We provide in this dataset the complete records from the top 120 m of twoice cores drilled on two adjacent ice rises (Hammarryggen and Lokeryggen, ~100 km apart) located in coastal Dronning Maud Land, Antarctica. Density, water stable isotopes (δ 18 O, δD and d-excess), ions concentrations (Na + , K + , Mg + , Ca + , MSA, Cl - , SO 4 2- and NO 3 - ), and continuous electrical conductivity measurement (ECM) records, as well as age models and resulting surface mass balance (SMB) are presented here. These ice cores are dated back to the end of the eighteenth century (CE 1793 ± 3 years for FK17and 1780 ± 5 years for TIR18) by manual and automatic multivariable layer counting and volcanic tie points validation. The SMB is calculated after correction for vertical strain rates. A detailed description of the measurement procedures, data treatments and uncertainties can be found in: Wauthy S., Tison, J.-L., Inoue, M., El Amri, S., Sun, S., Claeys, P., and Pattyn, F.:Physico-chemical properties of the top 120 m of two ice cores in Dronning Maud Land (East Antarctica): an open window on spatial and temporal regional variability of environmental proxies, submitted to Earth System Science Data (ESSD). These new records can be compared to those from other coastal ice cores in DML and to regional or global model results, and represent a great opportunity for further studies addressing the mechanisms behind SMB spatial and temporal variability in East Antarctica. The study was funded in the framework of the Mass2Ant project, contract n° BR/165/A2 by the Belgian Science Policy BELSPO.